The features of Khachaturian's film music - Arzumanyan, Վովա Արթուրի (Musical Armenia, 2025)
In recent decades, it has been almost impossible to imagine cinema without musical accompaniment. Often, music becomes a key element in solidifying certain scenes from films in memory and not only. A significant number of films gain their content value through music. Taking all of this into account, we have explored Aram Khachaturian's creative works as a film composer, highlighting the aesthetic and cinematographic features of his works. Through the example of specific compositions, we have attempted to encapsulate the importance and relevance of his legacy in film music. By analyzing Khachaturian's film music within the context of film history, we have sought to distinguish its logical and content interconnections according to the films, which contribute to the ideological completion of the films. Our goal is also to provide a comprehensive view of the history of Khachaturian's film music.